Fibroblast growth factor 23 levels before and after renal transplantation - Mohamed M El-khatib; Amal R El-Shahaby; Sahier O EEl-Khashab; Eman El Mohamed; Amr M Shaker (SpringerOpen, 2016)
Background Fibroblast growth factor 23 (FGF23), a novel bone-derived hormone that inhibits phosphate reabsorption and calcitriol production by the kidney, has uncovered primary regulatory pathways and new systems biology governing bone mineralization, vitamin D metabolism, parathyroid gland function, and renal phosphate handling. Aim of the work The aim of the present prospective study was to investigate FGF23 levels in patients with end-stage renal disease before and after a successful renal transplant and their probable association with the markers of bone and mineral metabolism. Patients and methods A total of 40 patients were studied for 6 months and divided into two groups (hemodialysis vs. renal transplant patients). Serum FGF23, calcium, phosphorus, and intact parathyroid hormone (iPTH) were estimated for both groups. We compared the changes in serum FGF23, calcium, phosphorus, and iPTH in renal transplant patients 3 and 6 months after successful renal transplantation. Results The serum FGF23 decreased significantly after renal transplantation. iPTH and P levels also decreased significantly after renal transplant, whereas Ca level increased. Conclusion FGF23 levels were markedly increased in patients with end-stage renal disease associated with an increase in phosphorous and iPTH levels. FGF23 levels decrease dramatically after successful renal transplantation and remain within the normal limits when graft function is good. iPTH and P levels also decrease significantly after renal transplantation, whereas Ca increases.